AMPK synergizes with the combined treatment of 1′‐acetoxychavicol acetate and sodium butyrate to upregulate phase II detoxifying enzyme activities. Issue 7 (5th April 2013) - Yaku, Keisuke; Matsui‐Yuasa, Isao; Konishi, Yotaro; Kojima‐Yuasa, Akiko
Abstract : Scope: Phase II enzymes play important roles in detoxifying xenobiotics. We previously reported that both 1'‐acetoxychavicol acetate (ACA) and sodium butyrate individually increased phase II enzyme activities. Here, we determined the combined action of ACA and sodium butyrate on phase II enzyme activities in intestinal epithelial cells (IEC 6). Methods and results: ACA and sodium butyrate synergistically increased phase II enzyme activities. Protein levels of intranuclear transcription factor NF‐E2–related factor 2 (Nrf2) were increased by ACA or sodium butyrate treatment, but treatment with both did not produce a synergistic effect. Intranuclear p53 protein levels were increased by ACA but decreased by sodium butyrate alone or combined treatment with ACA and sodium butyrate. In contrast, p53 acetylation was promoted by sodium butyrate and the ACA and sodium butyrate combination. Inhibition of AMPK activity decreased phase II enzyme activities that were upregulated by treatment with ACA plus sodium butyrate or other phytochemicals, including kaempferol, quercetin, and epigallocatechin‐3‐gallate. Combined treatment with ACA and sodium butyrate increased phosphorylated AMPK levels. Conclusion: These results suggest that ACA and sodium butyrate synergistically contribute to xenobiotics metabolism. The combined ACA and sodium butyrate treatment synergistically upregulated phase II enzyme activities through AMPK activation and p53 acetylation.